Study of feto-maternal outcome in previous cesarean section - Chiniwar, Mahantappa A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: There is increase in number of primary cesarean sections, leading to more number of women facing the issue of mode of delivery in the current pregnancy. There are reports about success of vaginal birth after cesarean section as well as complications such as scar dehiscence, rupture of uterus, poor maternal and fetal outcome. Methods: A prospective study was done for a period of 1 yr and 9 months at Cheluvamba Hospital attached to Govt Medical College Mysore from October 99 to June 2000. Data regarding previous cesarean section was collected, clinical findings during the present pregnancy were noted. Results: During the study period there were 942 women admitted with previous history of cesarean section. Elective repeat cesarean section was done for 530 cases and trial of labour after cesarean section was planned for 412 cases. Successful vaginal delivery was conducted in 311 cases. Repeat emergency cesarean section was done for 96 cases due to failed trial of labour. Maternal morbidity such as adhesions was seen in 11.25% and obliteration of U V fold in 7.92% of cases. Maternal mortality was seen in 0.15%. Perinatal morbidity was seen in 3.32%, perinatal mortality in 3.96%. Conclusions: With increasing proportion of women with previous cesarean sections, it is essential to counsel these women during trial of vaginal delivery in well equipped hospitals. It is worth to reduce primary cesarean section to avoid complications in consequent pregnancies. Proper and timely decision for repeat cesarean sections will reduce fetal and maternal morbidity and mortality.